ENSAIOS DE PROFICIÊNCIA NA ACREDITAÇÃO DE LABORATÓRIOS DE CALIBRAÇÃO: INVESTIGAÇÃO DAS CAUSAS-RAIZ DE RESULTADOS INSATISFATÓRIOS - Silva, Mario Antônio Fernandes da (2009)
Accreditated laboratories must demonstrate to the accreditation body that they are competent to carry out calibrations and tests defined in their scopes. Proficiency Tests activities are one of the main tools to evaluate its performance and competence of these laboratories. In the calibration laboratories accreditation process, measurement audits, one of the proficiency test activities, are used in the making process decision, but it is becoming a worrying factor for maintenance the time scales of accreditation process, because of the time spent for the treatment of unsatisfactory results obtained by the laboratories. The content of the present study points out the root causes of unsatisfactory results performed by calibration laboratories accredited by Cgcre/Inmetro. The development of reference based on competence, systemic view of the laboratories and process improvement served as the basis for research with laboratories, as well as documentary research in the initial and maintenance accreditation processes of Cgcre/Inmetro, allowing to identify the laboratories performance on the investigation of causes, as well as the sources of unsatisfactory results. The treatment of the results obtained in research has demonstrated the relevance of the proficiency testing activities in its function of performance evaluation and the competence of calibration laboratories, in addition add the possibility to map the activities related to investigation in order to define a appropriated tool able to optimize work of identifying the root causes of unsatisfactory results.